Economic Activities of Kelakai (Stenochlaena Palustris) Chips to Support the Family Economy in Anjir Pasar Village - Rizkia Ananda Sari; Ersis Warmansyah Abbas; Rusmaniah Rusmaniah; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy (Universitas Lambung Mangkurat, 2024)
This article discusseswhat are the economic activities of the Kelakai (Stenochlaena Palustris) Chips Business in Anjir Pasar Village.StudyThis was done to describe the economic activities contained in the kelakai (Stenochlaena Palustris) chips business to support the family economy. The Anjir Pasar Village area was the location for this research. The method used in the research is a descriptive method, namely observation, interviews and documentation in obtaining data. The data analysis used was data reduction, presentation and verification as a conclusion. Testing the validity of the data in this research was carried out by triangulating sources, techniques and time. The research results show that the economic activities in kelakai chips are production, distribution and consumption. Production to make a kelakai plant into kelakai chips. Distribution as a distributor of kelakai chips to consumers. Consume as a casual chips connoisseur. The economic activity that occurs in kelakai chips can produce a source of income which can support the economy of the business owner's family and their team. These activities can be a source of income that supports the economy of the business owner's family and their team.